Transformation of the currency regulation regime and foreign economic relations of Russia in the context of expanding anti-Russian sanctions - O. B. Anikin; O. M. Fedin (Вестник университета, 2024)
The article discusses the features of currency regulation and foreign economic relations of the Russian Federation (hereinafter referred to as RF, Russia) in the context of the introduction and growth of anti-Russian sanctions by the United States of America, European Union countries and other unfriendly countries, issues related to ensuring the sustainability of the Russian economy and its ability to withstand negative internal and external influences, issues of financial security, which is an important component of the country’s economic security, issues of the current state of the state’s banking system and the Russian economy as a whole. The article also discusses the possible expansion of international economic relations between Russia, China, North Korea and other countries. The purpose of the article is to identify directions for the transformation of the currency regulation regime and foreign economic relations of the RF in the context of the expansion of anti-Russian sanctions. The subject of the study is the currency and foreign economic relations of the RF with friendly and unfriendly countries in the current conditions of growing anti-Russian sanctions and the conduct of a special military operation in Ukraine. In conclusion, the article highlights key changes associated with changes in Russia’s foreign exchange and foreign economic activeities, promising opportunities for further expansion of international economic relations with China, the Democratic People’s Republic of Korea and other friendly countries.